The effect of habitat on trapper behaviour and marten harvesting success in northern Ontario - Wiebe, Philip Andrew (University of Guelph, 2009)
This thesis is an investigation of habitat preference by American marten ('Martes americana'), the humans that trap them, and the effect of habitat on capture rates by trappers. Marten face predation by several wild carnivores, but are killed most often by human fur trappers. I found that marten in northern Ontario preferred old mixed forest stands, with preference peaking around 85 years of stand age and conifer proportions 50 to 65%. Trappers targeted habitat preferred by marten while setting traps, and preferred coniferous patches within mixed stands that were close to vehicular access. The-removal method was used to estimate marten population density and vulnerability to trapping. Vulnerability of marten to trapping was negatively associated with temperatures during the trapping period but showed no correlation with prey availability. Harvest success was not positively associated with habitat specific probability of use by marten.